2009
DOI: 10.3340/jkns.2009.45.5.312
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Disc Herniation Producing Acute Brown-Sequard Syndrome

Abstract: J Korean Neurosurg Soc 45 : [312][313][314] 2009 Brown-Sequard syndrome may be the result of penetrating injury to the spine, but many other etiologies have been described. This syndrome is most commonly seen with spinal trauma and extramedullary spinal neoplasm. A herniated cervical disc has been rarely reported as a cause of this syndrome. We present a case of a 28-year-old male patient diagnosed as large C3-C4 disc herniation with spinal cord compression. He presented with left hemiparesis and diminished… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…The frequency of this syndrome has been reported to be 2.6% and 0.21% by Jomin et al and Kim et al, respectively. 6 A review of the literature associated with BSS caused by herniated cervical disc indicates that C5-C6 is the most vulnerable in discogenic BSS, 3,4,6 and that most cases with no or insignificant radicular symptoms resulting from the neural compression seen in most patients of which was primarily paracentral herniation on the spinal cord itself and not the nerve root. 7 In addition, most cases of discogenic BSS were related to extradural herniation, which seemed to be associated with complete neurological recovery more often compared with these intradural herniation, either an anterior approach or a posterior surgery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The frequency of this syndrome has been reported to be 2.6% and 0.21% by Jomin et al and Kim et al, respectively. 6 A review of the literature associated with BSS caused by herniated cervical disc indicates that C5-C6 is the most vulnerable in discogenic BSS, 3,4,6 and that most cases with no or insignificant radicular symptoms resulting from the neural compression seen in most patients of which was primarily paracentral herniation on the spinal cord itself and not the nerve root. 7 In addition, most cases of discogenic BSS were related to extradural herniation, which seemed to be associated with complete neurological recovery more often compared with these intradural herniation, either an anterior approach or a posterior surgery.…”
Section: Discussionmentioning
confidence: 99%
“…7 In addition, most cases of discogenic BSS were related to extradural herniation, which seemed to be associated with complete neurological recovery more often compared with these intradural herniation, either an anterior approach or a posterior surgery. 3,4,6,7 Presenting syndromes of spinal cord injury are based on the functional anatomy, and a basic knowledge of spinal cord anatomy is essential for interpretation of clinical signs and symptoms and understanding of pathologic processes involving the spinal cord. 8,9 Transverse injury of hemicord disrupts descending corticospinal tract has already crossed in the pyramidal decussations, resulting in upper motor neuron paralysis in the ipsilateral side below the level of the lesion, 1,[3][4][5][6]8,9 or combined with ipsilateral lower motor neuron weakness at the level of the lesion or above, 8,9 reflecting an injury of anterior horn.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acute cervical disk presenting as acute Brown-Séquard syndrome is rarely described in case reports. 11,12,14,15 Abouhashem et al reported seven cases of disk herniation causing acute Brown-Séquard syndrome. 15 Their review described 45 cases of disk herniation resulting in hemisyndrome reported since 1928.…”
Section: Discussionmentioning
confidence: 99%
“…BSS is usually characterized by ipsilateral motor weakness, loss of proprioceptive and vibratory sensation, as well as loss of contralateral pain and temperature sensation 1 . BSS is most commonly seen in patients with spinal trauma and extramedullary spinal neoplasm [2][3][4] .…”
Section: Introductionmentioning
confidence: 99%